Structure elucidation and topological studies of new lanthanide-organic frameworks (UPMOFs) synthesised via solvothermal route using mixed dicarboxylate linkers of 1,4-benzenedicarboxylic acid and 4,4-oxybis benzoic acid - Raman, Velan; Natasya Muhamad Khirudin, Nurul; Nabihah Mohamad Ishak, Nurul; Begum SA Ravoof, Thahira; Basyaruddin Abdul Rahman, Mohd; Ibrahim Mohamed Tahir, Mohamed (Elsevier BV, 2024)
The new lanthanide-organic frameworks (UPMOFs) were solvothermally synthesised using M(NO3)3·6H2O (M = La, Ce, Pr and Nd) metal salts with mixed dicarboxylate ligands namely, 1,4-benzenedicarboxylic acid (H2BDC) and 4,4-oxybis benzoic acid (H2OBA). The successful synthesis produced a series of four three-dimensional (3D) UPMOFs identified as La(BDC)(OBA)(H2O)2.H2O (UPMOF710 (1)), Ce(BDC)(OBA)(H2O)2.H2O (UPMOF711 (2)), Pr(BDC)(OBA)(H2O)2.H2O (UPMOF712 (3)) and Nd(BDC)(OBA)(H2O)2.H2O (UPMOF713 (4)). Comprehensive characterisations were performed on the newly synthesised UPMOFs, encompassing techniques such as infrared spectra (IR), powder X-ray diffraction (PXRD), thermal gravimetric analysis (TGA), scanning electron microscopy (SEM), Brunauer-Emmet-Teller (BET) and the structural elucidation was conducted using single-crystal X-ray diffraction (SCXRD). Notably, all four 3D UPMOFs were crystallised in a monoclinic sytem with different space groups. The UPMOFs (1) had a P21/n space group while the 2–4 were crystallised in the space group of I2/a. Consequently, the 2–4 UPMOFs are classified as isostructural MOFs. Remarkably, the topological analysis unveiled a novel topology denoted as upm, which has not been observed in the realm of reticular chemistry.